Organic spectroscopy - Kemp, William, 1932- (New York : Palgrave, 1975)
New features of the third edition include: * 100 new student exercises, worked examples and problem exercises * An expanded chapter on nuclear magnetic resonance * Details of the latest developments in Fourier transform instrumentation.
"A Halsted Press book."
First edition 1975
Reprinted six times
Second edition 1987
Reprinted once
Third edition 1991
Includes bibliographies and index.
PHR
Book Finder International
Keywords: Spectrum analysis; Chemistry, Organic; Pharmacy